Hubungan Beban Kerja dengan Kelelahan Pada Guru Sekolah Dasar di Kecamatan Motoling Barat - Rendy Mogogibung; Richard Andreas Palilingan; Merdekawati Evangli Weken (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: High workload without proper management can potentially cause work fatigue among teachers, which ultimately impacts productivity and the quality of learning in schools. This study aims to determine the relationship between workload and work fatigue among elementary school teachers in West Motoling District. Methods: The population in this study is all elementary school teachers in West Motoling District, totaling 133 teachers. The sample size was determined using the Solvin formula, resulting in 57 teachers, and respondents were selected through accidental sampling. Data collection was conducted using two types of questionnaires: NASA-TLX to measure workload and IFRC to measure work fatigue. Data analysis was performed using Spearman Rank correlation test. Results: The results show that the majority of teachers experience workload in the very high category at 61%, while the level of work fatigue is predominantly in the Low category at 68%. The Spearman Rank test yielded a correlation coefficient of 0.054 with a p-value of 0.690, Conclusion: indicating no significant relationship between workload and work fatigue among elementary school teachers in West Motoling District.